Desempenho hidráulico de unidades gotejadoras com efluente doméstico tratado e prevenção do entupimento - Silva, Ketson Bruno da (2017)
Brazil faces typical problems of a developing society in relation to water scarcity. This situation intensifies in the northeast region, due to its climate and the lower incidence of rainfall. Reusing water is a way to control losses and avoid waste. Their reuse in agriculture can be a very effective strategy for preserving water resources and reducing their indiscriminate use. An alternative to reduce the risks of contamination of agricultural crops is the use of drip irrigation systems. In this context, the present work had as objective to study the hydraulic performance of dripping units with treated domestic effluent and prevention of clogging. Two experimental stands were set up in an area located in the East Campus of the Universidade Federal Rural do Semi – Árido, Mossoró/RN, to evaluate the hydraulic performance and clogging of four types of drippers every 80 h, applying treated domestic wastewater (ARDT), For a total of 400 hours. The experiment was set up in a sub - divided plots scheme, with treatments: T1 - without application of the product, T2 - 100ml of Byosol Swift in 50L of water, T3 - 200ml of Byosol Swift in 50L of water, and T4 - 300ml of Byosol Swift in 50L of water. In the subplots the types of drippers: G1 - flow of 1,60 L h-1, G2 - flow of 2.00 L h-1, G3 - flow of 1,60 L h-1, and G4 - 70 L h-1, and in the subsubparcels the evaluation periods: 0, 80, 160, 240, 360 and 400 h. At each time, physical-chemical and microbiological analyzes of treated domestic wastewater were also carried out. Data were submitted to simple and multiple regression analysis, mean test and Pearson parametric correlation test. The results indicated that the null (mean), cubic, quadratic and linear regression models were the ones that best fit the analyzed variables, depending on the dosages of the product. The elements Fe, SD, SS, Ca2+ and pH predominated in the empirical models of hydraulic performance for the four types of drippers. There was no difference between treatments. The changes in the analyzed variables were due to the time of operation and the physical-chemical agents, which caused partial clogging of the drippers and, consequently, increase in the coefficients of variation of the flow of the drippers in the irrigation units that operated with ARDT. The action of the enzymatic catalyst was inhibited due to the high chlorine content present in the ARDT. The chemical elements, chlorine, potassium, calcium, silicon, iron and sulfur predominated in the chemical composition of the biofouling present in the analyzed drippers. The service pressures verified upstream and downstream of the screen filter of the irrigation system have inverse behavior over time